2010
DOI: 10.1007/s12070-010-0097-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of Juvenile Nasopharyngeal Angiofibroma: A Five Year Retrospective Study

Abstract: Juvenile nasopharyngeal angiofibroma is a pathologically benign yet locally aggressive and destructive vascular lesion of head and neck region typically affecting adolescent boys. The present article is a retrospective study of surgically treated patients of juvenile nasopharyngeal angiofibroma over a period of 5 years. The study discusses about most common presenting complaints, correlation of preoperative radiological and intraoperative staging and factors affecting recurrence of juvenile nasopharyngeal angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…This is because all stages of JNA express various types of SSTRs (SSTR 1, 2, 3, 5) in its stromal cells strongly compared to the proliferating new vessels 6 . A decreasing non‐significant trend for DOTANOC uptake was noticed with increasing age indicating that the age per se has some influence on tumor biology (Spearman correlation coefficient r = −0.19, P = .44) and its receptor expression similar to previous literature 9,21 …”
Section: Discussionsupporting
confidence: 83%
“…This is because all stages of JNA express various types of SSTRs (SSTR 1, 2, 3, 5) in its stromal cells strongly compared to the proliferating new vessels 6 . A decreasing non‐significant trend for DOTANOC uptake was noticed with increasing age indicating that the age per se has some influence on tumor biology (Spearman correlation coefficient r = −0.19, P = .44) and its receptor expression similar to previous literature 9,21 …”
Section: Discussionsupporting
confidence: 83%
“…JNA was the commonest benign nasopharyngeal tumour of the nasopharynx [5]. Planning of surgical approach depends on size and extent of the tumour as assessed by radiological investigations [8]. Surgical outcome of patients treated by external and endoscopic approaches is same with no complications or recurrences in a mean follow up period of 6.5 months.…”
Section: Resultsmentioning
confidence: 99%
“… 9 In a study of eight patients that underwent pre-operative embolization of the ipsilateral maxillary artery utilizing absorbable gelfoam, six experienced considerably less bleeding during surgical resection. 2 A recent systematic analysis of 131 cases within 57 studies over 21 years showed that the average blood loss in patients that underwent pre-operative embolization during purely endoscopic surgical resection averaged 406.7 mL compared to 828.3 mL in non-embolized patient undergoing purely endoscopic resection. 1 Furthermore, in open surgical cases there was less blood loss after preoperative embolization with an average of 685.0 mL compared to an average of 1912.1 mL lost in patients that did not undergo embolization.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologically, the tumor is comprised of haphazardly arranged vascular channels surrounded by dense paucicellular fibroblastic stroma, with the myofibroblast being the principal cell. 2,3 The bleeding propensity of these tumors is due to the findings that the smaller vessels in the center of the lesion tend to lack muscular elastic lamina, predisposing these vessels without a muscular surrounding layer that may otherwise assist in vasoconstriction to uncontrolled bleeding. 2 The blood supply to these lesions is derived from the internal maxillary artery, 8,9 a branch off the external carotid artery.…”
Section: Introductionmentioning
confidence: 99%